Pengaruh Teknik Audit Berbantuan Komputer, Kinerja Auditor, dan Locus of Control Terhadap Kualitas Audit Syariah - Farhan Zulfahmi; Cris Kuntadi (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
The digital era has brought significant transformation in various aspects of life, including in the world of sharia auditing. Advances in information and communication technology (ICT) open up new opportunities to optimize the sharia audit process through computerization. This research aims to examine the role of technology, the number of information systems, and the level of technological integration in the development of the computerized sharia audit process. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are that this research shows that computer-assisted audit techniques have no influence on audit quality. Meanwhile, auditor performance and locus of control have a positive and significant influence on audit quality.